1985
DOI: 10.1007/bf01320482
|View full text |Cite
|
Sign up to set email alerts
|

Value of computed tomography in the detection of complications of Crohn's disease

Abstract: Abdominal and pelvic computed tomography (CT) scans were performed on 17 patients with suspected complications of Crohn's disease. CT was superior to conventional barium studies and colonoscopy in demonstrating mural, serosal, and mesenteric pathology such as bowel wall thickening (100%), abscess (59%) and phlegmon (6%) formation, and fibro-fatty proliferation of the mesentery (41%). While not advocated as the primary means of evaluating Crohn's disease, CT can provide information vital to the management of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 9 publications
0
11
1
1
Order By: Relevance
“…Using other cross-section imaging methods, such as CT or magnetic resonance imaging (MRI), mesenteric fat hypertrophy has been described as a change in density of the tissue surrounding the bowel walls. 7,12,18,19 However, unlike some of these studies, we have not reported the US degree of the density of mesenteric fat or the quantification of the intraabdominal fat accumulation, since US is less objective and lacks the panoramic view of CT and MRI. Therefore, we assessed only the absence or presence of this condition, considering it present when a Ͼ5-6 mm hyperechoic halo around the thickened bowel walls was visible.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Using other cross-section imaging methods, such as CT or magnetic resonance imaging (MRI), mesenteric fat hypertrophy has been described as a change in density of the tissue surrounding the bowel walls. 7,12,18,19 However, unlike some of these studies, we have not reported the US degree of the density of mesenteric fat or the quantification of the intraabdominal fat accumulation, since US is less objective and lacks the panoramic view of CT and MRI. Therefore, we assessed only the absence or presence of this condition, considering it present when a Ͼ5-6 mm hyperechoic halo around the thickened bowel walls was visible.…”
Section: Discussionmentioning
confidence: 56%
“…Using different imaging methods, such as CT, the presence of increased fat density has been assessed in 25%-41% of CD patients. 7,18,19 Moreover, surgical series 2 identified fat wrapping in 70% of bowel resections. Undoubtedly, besides the methods used to assess mesenteric fat hypertrophy, the prevalence of this condition in CD also depends on patient selection.…”
Section: Discussionmentioning
confidence: 98%
“…Abdominal MDCT is the modality of choice for an acutely ill CD patient presenting in the emergency room. The MDCT findings correlate well with disease activity (level B) [60,61,62]. Contrast-enhanced CT of the abdomen/pelvis or US are useful in acutely ill patients to rule out complications such as intra-abdominal abscesses (level B) [61,68,115,116].…”
Section: Monitoring In Symptomatic Patientsmentioning
confidence: 99%
“…CT scans are useful in patients with fulminant symptoms to detect bowel obstruction, perforation, or toxic colon distension (level B) [60,61,62]. Abdominal MDCT is the modality of choice for an acutely ill CD patient presenting in the emergency room.…”
Section: Monitoring In Symptomatic Patientsmentioning
confidence: 99%
See 1 more Smart Citation